VARIASI DAN DEGRADASI SUARA PANGGILAN KODOK JANGKRIK [HYLARANA NICOBARIENSIS (STOLICZKA, 1870)] ASAL PULAU ENGGANO (ANURA: RANIDAE) [Variation and degradation on advertisement calls of Cricket Frog, Hylarana nicobariensis (Stoliczka, 1870) from Enggano Island] - Kurniati, Hellen; Hamidy, Amir (BERITA BIOLOGI, 2016)
Frogâs group of Hylarana nicobariensis (Stoliczka, 1870) is a complex species that has diverse genetic populations and variations on advertisement calls. Variations on advertisement calls among populations have been reported in Sumatra, Java and Bali. The population of frog in Enggano has different phenomenon that was not found in Sumatra and Java. Â Enggano population was genetically identical, but the advertisement calls were very diverse. There were four types of advertisement calls on the population in Enggano Island, namely: (1) advertisement call type 1 which has pulse wave with the dominant frequency of 2855.13 Â± 135.22 Hertz; (2) advertisement call type 2 which has pure tone wave with the dominant frequency of 2720.29 Â± 97.69 Hertz; (3) advertisement call type 3 which has pulse wave with dominant frequency 2634.61 Â± 292.81 Hertz; (4) advertisement call type 4 which has pure tone wave with dominant frequency 1618.79 Â± 83.05 Hertz. The degradation of the dominant frequency and the lower frequency was likely due to the increase of snout to vent length (SVL) of adult male that were followed by increasing the size of the head.